A large-scale experiment demonstrates that line marking reduces power line collision mortality for large terrestrial birds, but not bustards, in the Karoo, South Africa. Issue 1 (31st January 2021) - Shaw, Jessica M; Reid, Tim A; Gibbons, Bradley K; Pretorius, Matt; Jenkins, Andrew R; Visagie, Ronelle; Michael, Michael D; Ryan, Peter G
Abstract: Line markers are widely used to mitigate bird collisions with power lines, but few studies have robustly tested their efficacy. Power line collisions are an escalating problem for several threatened bird species endemic to southern Africa, so it is critical to know whether or not marking works to adequately manage this problem. Over 8 yr, a large-scale experiment was set up on 72 of 117 km of monitored transmission power lines in the eastern Karoo, South Africa, to assess whether line markers reduce bird collision mortality, particularly for Blue Cranes ( Grus paradisea ) and Ludwig's Bustards ( Neotis ludwigii ). We tested the 2 marking devices commonly used in South Africa: bird flappers and static bird flight diverters. Using a before-after-control-impact design, we show that line marking reduced collision rates for Blue Cranes by 92% (95% confidence interval [CI]: 77–97%) and all large birds by 51% (95% CI: 23–68%), but had no effect on bustards. Both marker types appeared similarly effective. Given that monitoring at this site also confirmed high levels of mortality of a range of species of conservation concern, we recommend that marking be widely installed on new power lines. However, other options need to be explored urgently to reduce collision mortality of bustards. Five bustard species were in the top 10 list of most frequently found carcasses, and high collision rates of Ludwig's Bustards (0.68 birds km –1 yr –1 uncorrected for survey biases) add to wider concerns about population-level effects for this range-restricted and Endangered species. Lay Summary: Power line collision mortality is a serious and accelerating bird conservation problem globally, particularly in the developing world with rapidly expanding electricity networks and high avifaunal diversity. Line marking is the most widespread collision mitigation measure employed worldwide, but there have been relatively few systematic tests of its efficacy. We set up a large-scale experiment in South Africa with a before-after-control-impact design on 72 km of transmission power line over 8 years to test two marking devices for reducing collisions of large terrestrial birds. Line marking reduced overall bird mortality by 51%, and Blue Crane mortality by 92%, but was not effective for bustards. Line marking should therefore be widely deployed, but alternative mitigation measures are urgently required for bustards that are threatened all over the world by collisions.